DESIGNING ADVENTURE PARK AS EDUCATIONAL TOURISM IN CITRA GRAND GALLESONG, MAKASSAR: ANALYSIS OF PSYCHOMOTOR, AFFECTIVE, AND COGNITIVE ASPECTS IN DESIGN - Punky Rahadianto; Silia Yuslim; Olivia Seanders; Etty Indrawati (Universitas Trisakti, 2024)
-